Electronic pain questionnaires: a randomized, crossover comparison with paper questionnaires for chronic pain assessment. - Cook, Andrew J; Roberts, David A; Henderson, Michael D; Van Winkle, Lisa C; Chastain, Dania C; Hamill-Ruth, Robin J (PAIN, 2004)
Electronic questionnaires for pain assessment are becoming increasingly popular. There have been no published reports to establish the equivalence or psychometric properties of common pain questionnaires administered via desktop computers. This study compared responses to paper (P) and touch screen electronic (E) versions of the Short-Form McGill Pain Questionnaire (SF-MPQ) and Pain Disability Index (PDI), while examining the role of computer anxiety and experience, and evaluating patient acceptance. In a randomized, crossover design 189 chronic pain patients completed P and E versions of the SF-MPQ and PDI, and self-ratings of anxiety, experience, relative ease and preference. Psychometric properties were highly similar for P and E questionnaires. For the SF-MPQ, 60% or more of subjects gave equivalent responses on individual descriptors and PPI scale, with 80% rating within +/-1 point for an 11-point VAS. Correlations for the SF-MPQ scales ranged from 0.68 to 0.84. For the PDI, 60% or more of subjects responded within +/-1 point on individual questions, and the total score correlation was 0.67. Comparison of mean difference scores revealed no significant differences between modes for any of the questionnaire items or scores. Anxiety and experience scores showed no significant associations through correlations and high/low comparisons. Although nearly half of subjects reported no computer training, anxiety ratings were low, and considerably more subjects rated the E questionnaires as easier and preferred. Findings are consistent with test-retest reliability data, and support the validity and acceptance of electronic versions of the SF-MPQ and PDI.